The Effectiveness of the Concept Mapping Technique in Improving the Competence of Writing Expository Essays for High School Students - Anggit Aruwiyantoko (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2021)
This study aims to determine the effectiveness of the use of concept mapping techniques in improving the competence of writing exposition essays for class X SMA Negeri 1 Kasihan Bantul. This study uses an experimental approach. The experimental design used was Randomized Pretest-Posttest Control Group Design. There are two kinds of research variables, namely one independent variable in the form of concept mapping techniques and one dependent variable in the form of students' exposition writing competence. The sampling technique used is simple cluster random sampling. Collecting research data through the non-test method in the form of an assignment to write an exposition. The research instrument used was an essay assessment sheet accompanied by a rubric. The validity of the instrument used in this study is content validity in consultation with experts (expert judgment). Interrater technique was used to test the reliability of the instrument. The data analysis technique used t-test. The results showed that: (1) there was a significant difference between students' exposition writing competence before being taught using the concept mapping technique and after using the concept mapping technique with sig (p) < 0.05.